FEATURES OF MAGNETIC STRUCTURE OF SUNSPOTS GROUPS AT DEVELOPMENT OF SUSTAINED FLUXES HIGH ENERGY GAMMA RAY - Minasyants, G.S.; Minasyants, T.M.; Tomozov, V.M. (Academic Scientific Journal of Computer Science, 2020)
The research of magnetic structure of sunspots groups which were sources of three highest values of fluxes gamma ray with energy of photons >100 MeV for all the time of observations on Large Area Telescope (LAT), on board the Spacecraft (SC) Fermi Gamma-ray is conducted. At the same time observed fluxes of gamma ray had also the greatest duration of existence. For comparison, group of spots of similar magnetic class was attracted, but in the absence in it of events that are sources of gamma ray. As a result of the analysis, a characteristic feature of the structure of magnetic fields was revealed: it is that in these sunspots groups inside the region of one polarity there is a very close location of the magnetic field of the opposite polarity. This occurs in the consequence of the interpenetration of cores and umbrae, as concentrated magnetic field carriers, of one polarity inside the field of another polarity. Observations show the existence of a rather long neutral line with very high magnetic field gradients, which affect the growth of active processes in the sunspots regions and, most importantly, the growth of proton acceleration efficiency on high-speed shock fronts and shock waves of CME. Therefore, groups of magnetic class sunspots BD and BGD, having a structure of close interweaving of magnetic fields of opposite polarities, exhibit extreme activity and are proposed to allocate them into special subclasses - BDe and BGDe (extreme). In the absence of such a property in the magnetic field structure, there is no significant enhancement of activity in the sunspots groups of BD and BGD classes.